Application of dye-sensitized and perovskite solar cells on flexible substrates. (1st March 2018) - Lund, P D; Halme, J; Hashmi, G; Asghar, I; Miettunen, K
Abstract: In this paper, a review of applying dye-sensitized (DSCs) and perovskite solar cells (PSCs) on flexible substrates is presented. Metallic and polymeric materials are the most common flexible substrates used. Cell integration into a textile substrate is also considered here as a future alternative. Common challenges with these include penetration of humidity, cell stability, and lifetime. Flexible DSCs and PSCs are still a niche technology, but have an inherent potential for cheap roll-to-roll mass production of photovoltaics.